Efficiency of prediction by near-surface methods of hydrocarbon fields (Dnieper-Donetsky avlakogen, North-Skovtsivska area - Sunday structure) - I. D. Bagriy (Геофизический журнал, 2010)
Given the transition to the development of small-scale oil deposits, the problem of development and implementation of new techniques of mapping the promising hydrocarbon areas is quite urgent. The author has developed and implemented a number of low-cost near-surface express methods of research. The forecast maps for hydrocarbon search have been developed on the basis of structural thermo-atmo-geo-chemical research (STAGR). The efficiency of forecasting with near-surface methods was proved by the discovery of 2 productive oil wells in Severo-Skvortsovskaya area - the structure Nedelnaya.